Human footprint alters morphological traits and gut microbiome assembly of Antarctic sea urchins - Moya, Fernando; Schwob, Guillaume; Ugas-Bravo, Natalia; Delleuze, Melanie; Gerard, Karin Francoise; Jacquet, Stephanie; Poulin, Elie; Cabrol, Lea; Benitez, Hugo A. (My University, 2025)
Antarctica has experienced a growing human footprint in recent decades, driven by the intensification of scientific, logistic, and tourism activities. While the effects of human activities on Antarctic ecosystems are increasingly documented, their impact on developmental stability and microbiome of Antarctic species remains largely unexplored. Here, we compared two contrasting coastal sites in Fildes Bay, King George Island: one close to a research station, and the other within a protected area. Trace element concentrations in sediments were analyzed by ICP-MS. The Antarctic sea urchin Abatus agassizii was chosen as a model organism to assess the effects of human footprint, integrating two key aspects: (i) the sea urchin's fluctuating asymmetry (i.e. small random differences between specimen sides), as an indicator of developmental stress (n = 60), and (ii) its gut microbiome composition and assembly processes, through 16S rRNA amplicon sequencing (n = 26). Arsenic (As) and potassium (K) were significantly enriched in the sediment of the anthropogenically impacted site compared to the protected area. Higher levels of fluctuating asymmetry and shape variation were detected in A. agassizii individuals from the contaminated site, accompanied by alterations in gut microbiome, including destabilized cooccurrence network, increased variability and stochasticity, and enrichment of bacterial taxa typically associated with hydrocarbon exposure. These results highlight the potential of anthropogenic pollution to disrupt critical characteristics of a key sediment bioturbator such as A. agassizii. Abatus sea urchins may serve as valuable bioindicators for monitoring human-induced stress, guiding conservation efforts to limit the human footprint and protect these highly sensitive marine Antarctic ecosystems.
Keywords: anthropogenic activity; southern ocean; human footprint; bioindicator; trace metals; developmental instability; gut microbiome; protected area